(NsOWREMENNAQ RUSSKAQ ORFOGRAFIQ (B:s (Nu^EBNOE POSOBIE (B/s - (NiWANOWA(B, (NwERA fEDOROWNAs ((NmOSKWA (B:s (NwYS[AQ [KOLA(B,s, 1991)
(NbIBLIOGR(B. (NW KONCE GLAWs
Keywords: (NrUSSKIJ QZYKs -- (NoRFOGRAFIQs